Dostoevsky's Democracy - Ruttenburg, Nancy (Princeton University Press, 2010)
Dostoevsky's Democracy offers a major reinterpretation of the life and work of the great Russian writer by closely reexamining the crucial transitional period between the early works of the 1840s and the important novels of the 1860s. Sentenced to death in 1849 for utopian socialist political activity, the 28-year-old Dostoevsky was subjected to a mock execution and then exiled to Siberia for a decade, including four years in a forced labor camp, where he experienced a crisis of belief. It has been influentially argued that the result of this crisis was a conversion to Russian Orthodoxy and r